Phosphonates and Phosphonate Prodrugs in Medicinal Chemistry: Past Successes and Future Prospects - Krečmerová, Marcela; Majer, Pavel; Rais, Rana; Slusher, Barbara S. (Frontiers in Chemistry, 2022)
Compounds with a phosphonate (–P(O)(OH)2) group attached directly to the molecule via a P-C bond serve as suitable non-hydrolyzable phosphate mimics in various biomedical applications. In principle, these compounds often inhibit enzymes utilizing phosphates as substrates. In this review we focus mainly on biologically active phosphonates that originated from our institute (Institute of Organic Chemistry and Biochemistry in Prague) including antiviral acyclic nucleoside phosphonates (ANPs, e.g. adefovir, tenofovir, and cidofovir) as well as derivatives of non-nucleoside phosphonates such as 2-(phosphonomethyl) pentanedioic acid (2-PMPA) that originated from a collaboration between Johns Hopkins Drug Discovery and IOCB. When transformed into prodrugs by derivatizing their charged functionalities, all these compounds show potential to become drug candidates for the treatment of viral infections. ANP prodrugs with suitable pharmacokinetics include amino acid phosphoramidates, pivaloyloxymethyl (POM) and isopropoxycarbonyloxymethyl (POC) esters, alkyl and alkoxyalkyl esters, salicylic esters, (methyl-2-oxo-1,3-dioxol-4-yl) methyl (ODOL) esters and peptidomimetic prodrugs. We also focus on the story of cytostatics related to 9-[2-(phosphonomethoxy)ethyl]guanine and its prodrugs which eventually led to development of the veterinary drug rabacfosadine. Various new ANP structures are detailed including those being investigated as antiparasitics, especially antimalarial agents e.g. guanine and hypoxanthine derivatives with 2-(phosphonoethoxy)ethyl moieties, their thia-analogues and N-branched derivatives. In addition to ANPs and their analogs, we also describe prodrugs of 2-(phosphonomethyl)pentanedioic acid (2-PMPA), a potent inhibitor of the enzyme glutamate carboxypeptidase II (GCPII), also known as prostate-specific membrane antigen (PSMA). GCPII inhibitors, including 2-PMPA, have been found efficacious in various preclinical models of neurological disorders which are caused by glutamatergic excitotoxicity. Unfortunately, the highly polar character of 2-PMPA and hence its low bioavailability severely limits its potential for clinical use. To overcome this problem, various prodrug strategies have been used to mask the carboxylates and/or phosphonate functionalities of 2-PMPA with POM, POC, ODOL and alkyl esters. Chemistry and biological characterization led to identification of prodrugs with over 50-fold greater oral bioavailability, with the most promising being tetra-ODOL-2-PMPA.